Clinico-mycological study of otomycosis in Raichur, Karnataka: a hospital based study - Sangavi, Arvind Kumar B.; Peerapur, Basavaraj; Gummadi, Nirmita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Otomycosis is a fungal infection of the ear canal. It is mostly seen in hot and humid climatic conditions of the tropical and subtropical countries. It can also occur as a result of decreased immunity (and has been seen as a common occurrence as an opportunistic infection in the immunocompromised). Methods: Patients clinically diagnosed with otomycosis and coming to the ENT department RIMS teaching hospital were first subjected to detailed history taking. The samples from ear will then be collected by three sterile cotton swabs and sent to Microbiology Department, RIMS. Fungal, bacterial cultures were performed and microscopic examination was done. Results: Patients presented with a wide age range, the youngest patient being 6 months old and eldest being 28.31 years old. The mean age of the study population was 28.31 years. The ratio between male and female patients was 1.13:1 with male predominance. There were 26 patients (81.2%) who had a habit of using pins or sticks. The chief complaints of majority of the patients were pain and itching. Pain ranged from mild to severe type. Least common symptom was tinnitus. Conclusions: In our study male predominance was seen and majority of cases were unilateral. There were only 5 patients who were immunocompromised. The most common presenting symptom was pain and itching. There were 81.2% patients who had a habit of using pins/ sticks.